Pengembangan Sistem Pelaporan Pajak untuk Koperasi Sawit Berbasis Website - David John (UNIVERSITAS KALBIS, 2023)
This study aims to create a web-based tax reporting system application for palm oil cooperatives. This application can only be used for oil palm cooperatives because the business flow of each type of cooperative is different. The method used is Software Development Life Cycle (SDLC) and the development software used is Visual Studio Code with JavaScript programming language. The results obtained in this study are that this application can fulfill all workflows in palm oil cooperatives, has a complete transaction journal and can facilitate or speed up cooperative management in tax reporting